Perioperative Neuroprotection with Systemic Hypothermia During Carotid Endarterectomy - Alexey A. Syrovatsky; Ionas S. Simutis; Alexey V. Svetlikov; Konstantin M. Lebedinsky; Alexey N. Shcheglov; Vyacheslav A. Ratnikov; Daria E. Reznichek; Evgenia V. Khaldina (Общая реаниматология)
Prevention of brain injury during carotid endarterectomy (CEA) remains a significant challenge. Moderate controlled systemic hypothermia may serve as a potential neuroprotective measure during these procedures.Aim of the study. To investigate the neuroprotective effects of moderate systemic hypothermia during CEA.Materials and methods. Fifty-nine patients undergoing CEA under combined anesthesia were included. Patients were divided into two groups: the hypothermia group (N=33) and the normothermia control group (N=26). Both groups received standard measures to prevent cerebral ischemia. The hypothermia group received additional moderate systemic hypothermia aimed at a temperature range of 34–35°C. Cognitive function was assessed preoperatively and at 2, 5, and 30 days postoperatively using neurocognitive tests. Statistical analysis was performed with IBM SPSS Statistics.Results. The incidence of cognitive impairment was 21.1% in the hypothermia group and 26.9% in the normothermia group. Postoperative cognitive impairment was more common in the normothermia group: 15.38% on day 5 and 11.5% on day 30 postoperatively compared to 12.1% and 6.1% in the hypothermia group (P<0.05).Conclusion. This study demonstrated the neuroprotective effects of hypothermia, manifested by a reduced severity of cognitive impairment in the hypothermia group. Further research is needed to identify high-risk patients who would benefit most from this neuroprotective strategy and to optimize hypothermia protocols.